2015
DOI: 10.3329/seajph.v5i1.24846
|View full text |Cite
|
Sign up to set email alerts
|

A study on depression in people living with HIV/AIDS in South-West part of Uttar Pradesh, India

Abstract: HIV/AIDS and depression are often thought to be interlinked. HIV positive cases may trigger symptoms of depression which, in turn, may result in risky sexual behavior and spread of HIV. Interviews were conducted in 104 patients of HIV/AIDS at the Anti-Retroviral Therapy (ART) Clinic of a teaching hospital in Uttar Pradesh (India) to study depression and examine its prevalence and association, if any, with some socio-demographic and clinical variables. The tools used to assess anxiety and depression and their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 23 publications
9
23
1
Order By: Relevance
“…The relationship of lower CD4 levels and depression has been documented from different parts of the World [5,[29][30][31]. Although, some studies failed to find a significant association between depression and CD4 cells count [9,10]. The progression of HIV infection was poorer in patients suffering from depression in our study.…”
Section: Discussionsupporting
confidence: 39%
See 4 more Smart Citations
“…The relationship of lower CD4 levels and depression has been documented from different parts of the World [5,[29][30][31]. Although, some studies failed to find a significant association between depression and CD4 cells count [9,10]. The progression of HIV infection was poorer in patients suffering from depression in our study.…”
Section: Discussionsupporting
confidence: 39%
“…Among studies conducted in India, the prevalence was found to be 16% in Maharashtra, South-West Indian state [7]. Some Indian studies also report higher rates of depression, 49% to 67% [8][9][10][11]. Further comparison of the prevalence of depression between our and these studies is difficult due to different study instruments diagnosing depression, methodologies, study population, and clinical settings.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations